2016
DOI: 10.3390/ijerph13101011
|View full text |Cite
|
Sign up to set email alerts
|

Protection from Ultraviolet Radiation during Childhood: The Parental Perspective in Bavaria

Abstract: During childhood, parents play a vital role in sun protection of their children. Their guidance is essential for avoiding excessive exposure to ultraviolet (UV) radiation, a risk factor for developing skin cancer in later life. In a population-based cross-sectional study conducted between October 2011 and February 2012, we assessed how 3281 parents implemented sun protection for their three- to six-year-old children in practice. In particular, clothing, shade-seeking behavior, wearing of sunhats and sunglasses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
5
19
0
1
Order By: Relevance
“…Third, execution of parental sun protection behaviors was assessed using subjective, rather than objective measures. Together with a social desirability bias, the sensitivity of the themes could have induced a parental overestimation of their sun protection behaviors, as is also suggested in earlier work (93,94). To validate a potential over reporting among parents, studies comparing self-reported and objectively measured sun protection could be beneficial (95).…”
Section: Strengths and Limitationsmentioning
confidence: 84%
“…Third, execution of parental sun protection behaviors was assessed using subjective, rather than objective measures. Together with a social desirability bias, the sensitivity of the themes could have induced a parental overestimation of their sun protection behaviors, as is also suggested in earlier work (93,94). To validate a potential over reporting among parents, studies comparing self-reported and objectively measured sun protection could be beneficial (95).…”
Section: Strengths and Limitationsmentioning
confidence: 84%
“…A new index, the Garment Protection Factor, joins the two important aspects for determining the extent of sun protection offered by clothing, namely the quality of UVR blocking offered by the fabric and the coverage level of the body surface area due to clothing design, and informs the public about the sun-protective properties of clothing [ 37 , 38 ]. The difficulty for nurseries lies, however, in the fact that parents have to provide the necessary items, and as several studies have shown, parents themselves are often not aware of the importance of these two sun protection practices [ 14 , 39 ]. The fact that the majority of nurseries included the parents in the daily sun protection routine (by requesting to deliver the children with sunscreen applied or providing sunscreen) potentially indicates an increased awareness of the directors for the importance of a comprehensive sun protection strategy.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies in Germany have hitherto focused on the parental perspective on children’s sun protection at home and on the beach [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Since a high proportion of 3- to 6-year-old children in Germany are supervised for several hours per day in nurseries, the caregivers at the nurseries play an important role for daily sun protection of children at this age [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…En Estados Unidos se demostró mediante la evaluación de un grupo de 1255 menores de 20 años, una relación directamente proporcional entre el aumento de la radiación UV y el incremento del riesgo a desarrollar melanoma, debido a la transición de citidina a timidina, que genera dímeros de pirimidina de ciclobutano en el ADN (14) . En niños con exposición previa a radiación ionizante se ha observado que los tumores malignos secundarios más comunes fueron cáncer de piel no melanoma, cáncer de mama y tiroides, tumores óseos y tumores benignos del SNC, como meningiomas.…”
Section: Radiación Ionizanteunclassified